Association of sleep duration with stroke, myocardial infarction, and tumors in a Chinese population with metabolic syndrome: a retrospective study - Yingnan YE; Linxi ZHANG; Anping WANG; Yuxia Wang; Shiqing WANG; Guang NING; Yiming MU (Lipids in Health and Disease, 2020)
Abstract Background Previous studies have suggested that abnormal sleep duration is associated with increased risk of metabolic syndrome (MetS). However, evidence on the association of sleep duration with stroke, myocardial infarction (MI) and tumors in populations with MetS is limited. Methods A total of 8968 participants (2754 with MetS at baseline) were recruited in this retrospective study between March 2012 and December 2012. The baseline characteristics and information on sleep duration were collected by self-reported questionnaires. In addition, physical examination and blood test were also performed. The outcome events in this study were new onset of stroke, MI and tumors during subsequent follow-up. Multivariate logistic regressions were adopted to investigate the relationships between sleep duration and outcome events among different sleep duration groups (< 6 h, 6–7 h, 7–8 h [reference], 8–9 h, and > 9 h per day) in participants with MetS. Results The mean self-reported total sleep duration was 7.8 ± 1.2 h. Compared with participants with MetS slept for 7–8 h per day, the adjusted odds ratios (ORs) for those slept for > 9 h in stroke, MI and tumors were 2.014 (95% confidence interval [CI]: 1.184–3.426, P = 0.010), 1.731 (95% CI: 0.896–3.344, P = 0.102) and 2.159 (95% CI: 0.991–4.704, P = 0.053), respectively, whereas the adjusted ORs for those slept for < 6 h in stroke, MI and tumors were 2.249 (95% CI: 0.973–5.195, P = 0.058), 1.213 (95% CI, 0.358–4.104, P = 0.756) and 1.743 (95% CI, 0.396–7.668, P = 0.462), respectively. Conclusions Long sleep duration (> 9 h) significantly increased the risk of stroke but not MI and tumors in individuals with MetS compared with 7–8 h of sleep duration. Short sleep duration (< 6 h) was not associated with the increased risk of stroke, MI and tumors in individuals with MetS.